2020
DOI: 10.1590/1980-5373-mr-2019-0591
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Espresso Spent Ground Coffee Waste Extract Preparation and the Influence of its Chemical Composition as an Eco-friendly Corrosion Inhibitor for Carbon Steel in Acid Medium

Abstract: This work proposes the reuse of spent ground coffee waste (SCG) extracts as eco-friendly corrosion inhibitors for carbon steel in acid medium, and the correlation between their anticorrosive efficiency and chemical composition. The extraction method was optimized using a central composite design, and the chemical composition of the extracts was accessed using UV-Vis spectrometry, HPLC, and ICP-OES. EIS and Potentiodynamic Polarization (PP) tests evaluated the anticorrosive properties of the extracts. Total phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The articles found in the SciELO database describe the use of various materials as green inhibitors, as listed in Table 3. Among the possible inhibitors evaluated there were: coffee powder [32], caffeine [33], Aniba canelilla [34], Hibisco-colibri [35], mango and orange peels [36], garlic [37] and castor bean [38]. All materials (Table 3) were analyzed to discover whether they inhibit carbon steel corrosion in acid medium and showed inhibition efficiencies above 80%.…”
Section: Green Corrosion Inhibitorsmentioning
confidence: 99%
“…The articles found in the SciELO database describe the use of various materials as green inhibitors, as listed in Table 3. Among the possible inhibitors evaluated there were: coffee powder [32], caffeine [33], Aniba canelilla [34], Hibisco-colibri [35], mango and orange peels [36], garlic [37] and castor bean [38]. All materials (Table 3) were analyzed to discover whether they inhibit carbon steel corrosion in acid medium and showed inhibition efficiencies above 80%.…”
Section: Green Corrosion Inhibitorsmentioning
confidence: 99%
“…Ronga et al (2020), studied the valorization of SCG, to produce lightweight clay ceramic aggregates suitable for nursery grapevine production (Ronga et al, 2020). Da Costa et al (2020), reported the recycling of SCG as an eco‐friendly corrosion inhibitor for carbon steel. The obtained extract was found to have the best anti‐corrosion performance (94.83%) (Da Costa et al, 2020).…”
Section: Spent Coffee Grounds Valorizationmentioning
confidence: 99%
“…Da Costa et al (2020), reported the recycling of SCG as an eco‐friendly corrosion inhibitor for carbon steel. The obtained extract was found to have the best anti‐corrosion performance (94.83%) (Da Costa et al, 2020).…”
Section: Spent Coffee Grounds Valorizationmentioning
confidence: 99%
“…Extensive research in the literature highlights the considerable potential of used coffee grounds in producing value-added energy and non-energy-related products due to their significant content of fatty acids, cellulose, esters, lignin, and hemicelluloses [15][16][17]. Diverse investigations have been conducted to examine the corrosion-inhibitory efficacy of SCG extract across a spectrum of metals and within various environmental conditions [18][19][20][21][22]. According to research by Bouhlel et al [18,23], the hydro-alcoholic extract of used coffee grounds effectively protects C38 steel against corrosion in 1 M hydro-alcoholic acid.…”
Section: Introductionmentioning
confidence: 99%